2016
DOI: 10.1186/s13638-016-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

Channel modeling and power consumption analysis for galvanic coupling intra-body communication

Abstract: Intra-body communication (IBC), using the human body as the channel to transmit data, has lower power consumption, less radiation, and easier linking than common wireless communication technologies such as Bluetooth, ZigBee, and ANT + . As a result, IBC is greatly suitable for body area network (BAN) applications, such as the medical and health care field. Furthermore, IBC can be implemented in wearable devices, including smart watches, sports bracelets, somatic game devices, and multimedia devices. However, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…However, for obtaining reliable results these measurements should be repeated using small battery-powered devices and tested on a large group of individuals, in order to analyze the influence of anthropometric properties of a subject. It is expected that in capacitive IB2OB and IB2IB channels an intersubject variability (anthropometrical and bioelectric properties of a subject) will have higher impact on measurement results than in the case of a capacitive OB2OB channel (for which it is almost negligible [ 13 ]), as is the case with galvanic IBC channels [ 15 , 180 , 201 ].…”
Section: State Of the Art: Emerging Technologies For The Wbs Applimentioning
confidence: 99%
“…However, for obtaining reliable results these measurements should be repeated using small battery-powered devices and tested on a large group of individuals, in order to analyze the influence of anthropometric properties of a subject. It is expected that in capacitive IB2OB and IB2IB channels an intersubject variability (anthropometrical and bioelectric properties of a subject) will have higher impact on measurement results than in the case of a capacitive OB2OB channel (for which it is almost negligible [ 13 ]), as is the case with galvanic IBC channels [ 15 , 180 , 201 ].…”
Section: State Of the Art: Emerging Technologies For The Wbs Applimentioning
confidence: 99%
“…The measured attenuation was better when the subject was sitting compared to standing or walking, due to the difference in distance between the ground electrode and the external ground plane: the lower this distance is, the better the signal values are. Measurements of galvanic coupling IBC channel on 7 subjects were performed by Gao et al in [169,170]. It was shown that the thicker forearms had lower attenuation, which indicates that the main path of the IBC signals was muscle.…”
Section: Influence Of Anthropometric Characteristics and Positionmentioning
confidence: 99%
“…In summary, since in the galvanic coupling the signal is confined to the human body, for the same measuring setup the communication is mainly influenced by the anthropometrical and bioelectric properties of a subject, that is, intersubject variability [29,151,170]. For example, for IBC units placed on the arm these characteristics are arm diameter, tissue thicknesses (such as skin, fat, and muscle), tissue anisotropy, presence of joints in the communication channel, and so on [29,38,93,174].…”
Section: Influence Of Anthropometric Characteristics and Positionmentioning
confidence: 99%
“…As we previously stated, in this work we focus on galvanic coupling communication. From the literature, one can observe different studies related to galvanic communication [9][10][11][12][13][14][15]. The prominent and important problem addressed by the majority of these studies lies in modeling the body as a physical environment for the propagation of signals over short distances (up to 20 cm), performing an empirical analysis of the human tissue properties.…”
Section: Related Workmentioning
confidence: 99%
“…However, these devices are not suitable for data analysis [2,12]. When the applications handle specific data, such as medical or encrypted data [3], VNAs are replaced by data generation and acquisition systems [9,[12][13][14][15]. Reducing the size of this set is a challenge due to the transformers' physical characteristics.…”
Section: Introductionmentioning
confidence: 99%